Collaborative caching for distributed mobile database query processing - Elfaki, Mohamed Ahmed; Ibrahim, Hamidah; Mamat, Ali; Othman, Mohamed (2010)
As mobile applications are becoming increasingly widespread, the need for developing schemes to improve the performance and reliability for mobile database management increase.In addition, caching data in a wireless mobile computer adds an advantage to mobile applications by reducing the bandwidth requirement due to battery power limitation when disconnection occurred. In this paper, we investigate and propose an approach that supports distributed processing of a collaborative caching technique to enhance the process of continuous queries in mobile database environment in terms of average delay and hit ratio. Since our approach deals with continuous query, we propose a framework for improving the process of continuous query mechanism that caches and shares the query’s result among the nodes within the same cluster or with external database(neighbors cluster or ma in data server).